Status Besi pada Wanita Vegetarian di Kabupaten Badung Provinsi Bali - Ni Wayan Yogianti, Hamam Hadi, M.Dawam Jamil (Berita Kedokteran Masyarakat (BKM), 2003)
Background: It has been known that vegetarian do not eat meat and fish and related products considered to be good protein and iron sources. Whether iron status differs in vegetarian and non vegetarian women is unknown. Objective: This study was done to measure the difference in nutrient intakes and iron status between vegetarian and non vegetarian women.Methods: This observasional study was conducted in Badung regency, Bali in 2002. Subjects of this study consisted of 48 vegetarian and 48 non vegetarian women aged 18-45 years. Hemoglobin and ferritin levels of the subjects were measured at the begin-ning of the study and 3 months later.. Nutrient intake of women in both groups were collected using Food Frequency Questionnaire. Hemoglobinb level was measured us-ing cyanmethemoglobin method while serum ferritin was measured using ELISA method. Data analysise was conducted by using State 6.0 software.Results: The mean of protein intake in vegetarian women was 44.3 ± 13.8 gr/d (mean ± SD). The mean of protein intake in non vegetarian women was 62.8 ± 21.3 gr/d or 14.5 gr/d higher than that in vegetarian women (p< 0.05). The mean of iron intake originally from vegetables was 16.3 ± 7.0 mg/d and 9.8 ± 4.3 mg/d in vegetarian and non vegetarian respectively. While the mean of iron intake originally from animal prod-ucts was 0.03 ± 0.05 mg/d and 3.01 ± 2.06 mg/d in vegetarian and non vegetarian women respectively. The mean of serum ferritin in vegetarian women was 22.7 ± 15.1 µg/ml. However, the mean of serum ferritin in non vegetarian was 46.9 ± 28.7 ug/m1 or 25.4 pg/m1 higher than that in vegetarian women (p < 0.05). There was no significant difference in hemoglobin level between vegetarian and non vegetarian women.Conclusion: There were significant differences in protein and iron intakes between vegetarian and non vegetarian women. There was also a significant difference in serum ferritin but not in hemoglobin level between vegetarian and non vegetarian women. Keywords: protein and Iron intakes, ferritin, women, vegetarian